2009
DOI: 10.1186/1757-1626-0002-0000006553
|View full text |Cite
|
Sign up to set email alerts
|

Specific sublingual immunotherapy with peach LTP (Pru p 3). One year treatment: a case report

Abstract: Introduction: Food allergy is an increasing problem with limited therapeutic approaches apart from to the eviction diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Few papers have been published concerning peach sublingual immunotherapy and none with the specific target of legume desensitization. In 2009, Pereira et al described a LTPs-allergic patient who presented a negative double-blind placebo-controlled food challenge -acumulative dose of 150 grams of fresh peach-and a secondary good tolerance of legumes after four months of native Pru p3 specific sublingual immunotherapy with a maintenance dose of 200 µg of nPru p3 per month [10], similar to our monthly dose of 280 µg. One year later Garcia BE et al demonstrated changes in peach allergic patientsr Pru p3 IgE levels and in peach and apple extract SPT induced by a six month period of peach sublingual immunotherapy [11].…”
Section: Short Communicationmentioning
confidence: 61%
See 1 more Smart Citation
“…Few papers have been published concerning peach sublingual immunotherapy and none with the specific target of legume desensitization. In 2009, Pereira et al described a LTPs-allergic patient who presented a negative double-blind placebo-controlled food challenge -acumulative dose of 150 grams of fresh peach-and a secondary good tolerance of legumes after four months of native Pru p3 specific sublingual immunotherapy with a maintenance dose of 200 µg of nPru p3 per month [10], similar to our monthly dose of 280 µg. One year later Garcia BE et al demonstrated changes in peach allergic patientsr Pru p3 IgE levels and in peach and apple extract SPT induced by a six month period of peach sublingual immunotherapy [11].…”
Section: Short Communicationmentioning
confidence: 61%
“…Subsequently we undertook an open oral challenge with lentil and chickpea. We used lentil and chickpea soups in progressively increasing doses (1,5,10,30,75, and 125 mL) every 15 minutes according to previous studies [6]. Both challenges were negative.…”
Section: Short Communicationmentioning
confidence: 99%
“…There are some interesting cases showing the efficiency of this treatment, but there are no commercially available immunotherapies for these patients. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Pereira et al (12) published a case report of a woman with a positive allergological work-up for LTP and cross-reacting vegetable foods. The patient underwent SLIT for one year with efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, data on profilin content in plant-derived foods are lacking and for this reason we chose the maintenance dose of 100llg/mi weekly because 50llg/ml of profilin was the allergen concentration needed to induce a wheal double in size to the one induced by histamine at l Omg/ml in our patients (12).…”
Section: Discussionmentioning
confidence: 99%